Enhancement in amoxicillin adsorption and regeneration properties of SBA-15 after surface modification with polyaniline - Pandey, Prashant; Shankar, Aparajita; Biney, Michael; Saini, Vipin K. (Colloid and interface science communications, 2021)
In this study, the ordered-mesoporous silica SBA-15 was modified into a composite adsorbent (PANI-SBA-15) through in-situ polymerization of aniline inside its mesopores. During polymerization, the residual cationic species from SBA-15 were washed away, which increased the surface negative charge in PANI-SBA-15. It encouraged faster and higher adsorption of amoxicillin (34.2 mg·g−1) with PANI-SBA-15, as compared to SBA-15 (24.7 mg·g−1). The kinetics study shows that adsorption on PANI-SBA-15 follows pseudo-second-order rate expression and is regulated by the pore-diffusion mechanism. The adsorption mechanism was explained with changes in surface chemistry and kinetics of adsorption. The regeneration of exhausted PANI-SBA-15 with HNO3 is higher (up to 98%) as compared to SBA-15 (86%). The regenerated composite material were reused successfully without significant loss of its adsorption capacity (>80% after 6 cycles). The PANI-SBA-15 removed 64.7 to 70.8% impurities from different simulated hospital wastewater samples. [Display omitted] •The surface of mesoporous SBA-15 was modified with in situ polymerization of aniline.•Incorporation of polyaniline increased the negative charge and π-electrons density.•The modified nanocomposite PANI-SBA-15 shows faster adsorption with 38.5% higher adsorption capacity.•The exhausted nanocomposite was regenerated (98%) with HNO3 and reused several time.•The PANI-SBA-15 removed 64.7 to 70.8% of impurities from simulated hospital wastewater samples.